Dynamic source routing (DSR) protocol with euclidean effect in mobile ad hoc networks - Lee, Muhammad Hisyam; Olariu, Stephan; Salleh, Shaharuddin; Sanugi, Sahrorn (2000)
Node mobility in mobile ad hoc networks (MANETs) can cause frequent topology changes. therefore finding and maintaining the route(s) in such an environment is a challenging problem. In recent years, numerous ad hoc routing protocols have been proposed. This paper investigates the routing problem in a MANET by utilizing Euclidean effect to improve performance of routing protocols for MANETs. By using Euclidean information the proposed Euclidean Effect Routing (EER) protocols minimize disruptions of mobile multimedia when the network topology changes. One important feature of our protocol is the intermediate nodes of a route can perform rerouting before a path becomes invalid similar to that in well-studied cellular networks when it roams away to keep a route alive. This makes routes in the MANET more stable and insensitive to node mobility. We present an protocol based on the EER to choose the route that best meets the strict requirements of multimedia applications.